Perbandingan Model Eksponensial, Hiperbolik, Dan Logistik Dalam Memprediksi Pertumbuhan Populasi Kota Surakarta - M. Miftahul Huda; Kresna Oktafianto (Griya Journal of Mathematics Education and Application, 2026)
Population growth is a crucial factor in urban development planning. Surakarta City, as a rapidly developing city in Central Java Province, has experienced a continuous increase in population over time, making accurate population growth modeling essential. This study aims to model the population growth of Surakarta City using exponential, hyperbolic, and logistic models and to identify the best model based on prediction accuracy. The data used in this study are secondary population data of Surakarta City for the period 2017–2025 obtained from official publications of Badan Pusat Statistik. The parameters of each model are determined using the initial and final data of the observation period. Model performance is evaluated using the Mean Absolute Percentage Error (MAPE) to measure prediction errors. The results indicate that all three models adequately represent the population growth pattern of Surakarta City. The exponential model produces a MAPE value of 0.1632%, the hyperbolic model 0.1653%, and the logistic model 0.1664%. Based on these results, the exponential model is identified as the best model due to its lowest prediction error. Using the exponential model, the population of Surakarta City in 2026 is projected to reach 530,723 people. These findings are expected to support urban development planning and population policy decision-making.